2018
DOI: 10.1158/1055-9965.epi-18-0067
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal miR-27a and miR-130a Act as Novel Diagnostic and Prognostic Biomarkers of Colorectal Cancer

Abstract: Colorectal cancer is one of the most common cancers worldwide usually is associated with poor prognosis due to the advanced stage when diagnosed. This study aimed to investigate whether specific circulating exosomal miRNAs could act as biomarkers for early diagnosis of colorectal cancer. A total of 369 peripheral blood samples were included in this study. In the discovery phase, circulating exosomal miR-27a and miR-130a were selected after synthetical analysis of two GEO datasets and TCGA database. The differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 37 publications
(36 reference statements)
1
61
0
2
Order By: Relevance
“…Previous research has established that miR-27a-3p is implicated in the biological behavior of tumor cells in numerous cancer types. [29][30][31] Although research has also suggested that changes in miR-27a-3p expression are associated with the chemosensitivity of various malignancies, [32][33][34] the specific role that miR-27a-3p plays in the regulation of ADR resistance in BC has not been well established. Further research regarding the mechanisms of ADR resistance are needed so that effective agents can be developed to reverse chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has established that miR-27a-3p is implicated in the biological behavior of tumor cells in numerous cancer types. [29][30][31] Although research has also suggested that changes in miR-27a-3p expression are associated with the chemosensitivity of various malignancies, [32][33][34] the specific role that miR-27a-3p plays in the regulation of ADR resistance in BC has not been well established. Further research regarding the mechanisms of ADR resistance are needed so that effective agents can be developed to reverse chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant over‐expression of miR‐27a has also been identified in the exosomal species from cancer patients by several independent investigations. Liu et al . first proposed that circulating miR‐27a and miR‐130a served as potential prognostic and diagnostic biomarkers in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These vesicles, loaded with proteins and unique RNAs, have a wide range of biological functions, such as cell-to-cell communication [18]. Our previous study showed that circulating exosomal miR-27a and miR-130a were novel diagnostic and prognostic biomarkers of CRC [19]. However, specific miRNAs in serum exosome associated with LM have not been adequately investigated in CRC.…”
Section: Ivyspringmentioning
confidence: 99%